Individual Differences in Mixed Emotions Moderate the Negative Consequences of Goal Conflict on Life Purpose - Berrios-Espinoza, R (Elsevier Ltd, 2017)
Pursuing two incompatible goals (goal conflict) is commonly viewed as pernicious for individual well-being. Recent research has also shown that sometimes goal conflict instigates the experience of mixed emotions (co-activation of positive and negative emotions), and in turn, mixed emotions has been linked to some beneficial outcomes, including self-control and eudaimonic well-being. In the present study we formulated mixed emotions as an individual difference, and hypothesized that individual differences in mixed emotions can moderate the relationship between goal conflict and life purpose, a dimension of eudaimonic well-being. A sample of 73 individuals participated in an experience sampling study, producing over 2500 observations. Moderation analysis using multilevel modeling showed that goal conflict was negatively related to life-purpose, but more importantly this effect was qualified by a significant cross-level interaction, such that the negative effect of goal conflict on life purpose was weaker for individuals who commonly experienced greater mixed emotions. Given that conflicting goals are commonplace, experiencing mixed emotions may be beneficial for individuals. © 2017 Elsevier Ltd